Experimental and numerical investigation on seismic performance of semi-precast concrete sandwich shear wall. Issue 13 (October 2022) - Liu, Yun-Lin; Liu, Chang; Pan, Hao; Fu, Jia-Li; Huang, Jun-Qi; Hong, Jia-Qiang
This study investigated the seismic performance of an innovative semi-precast concrete sandwich shear wall (SCSSW) system. The system consists of two precast reinforced concrete (RC) wythes, a core cast-in-place RC wythe, a core thermal insulation layer, the fiber reinforced polymer connectors and the steel trusses. A total of three RC shear wall specimens were fabricated and tested under in-plane cyclic load. They consists of one conventional cast-in-place RC shear wall, one structural wythe of SCSSW (i.e., the assemble of a precast and a cast-in-place RC wythe), and one typical SCSSW. The failure mode, hysteretic curve, ductility and energy dissipation of the three specimens were studied and compared. Furthermore, numerical simulation based on multi-layer shell element was conducted to reproduce the test, and parametric analysis was conducted to facilitate a better understanding on the SCSSW. It was concluded that the SCSSW presented a ductile failure behavior; the seismic performance of the SCSSW including hysteretic curves, skeleton curves, stiffness degradation and the energy dissipation was similar to that of the cast-in-place RC shear wall, while the ductility of the SCSSW was slightly lower; and the facade precast RC wythe contributed few effect on the seismic performance of the SCSSW.